Catalytic reactions of platinum group metal phthalocyanines - Sekota, Mantoa Makoena C (Rhodes University, Faculty of Science, Department of Chemistry, 1999)
The voltammetric behaviour of I-cysteine and other organic compounds such as hydrazine, hydroxylamine and methionine has been studied on GCE modified with phthalocyanine complexes of osmium, rhodium and ruthenium. For cysteine oxidation, the catalytic activity of the electrode was dependent the nature of the axial ligand. When cyanide and dimethylsulphoxide (DMSO) were used as axial ligands, giving (DMSO)(Cl)Rh(III)Pc, [(CN)â‚‚Rh(III)Pc], (DMSO)â‚‚0S(II)Pc and [(DMSO)â‚‚Ru(II)Pc].2DMSO complexes, the peak current increased with repetitive scanning, indicating the increase in catalytic activity of the electrode after each scan. This behaviour was not observed when pyridine was used as axial ligand. The improvement of the catalytic activity of the GCE after the first scan has been attributed to the formation of the dimeric Ï€-cation radical species at the electrode surface. Water soluble phthalocyanine complex ([(CN)â‚‚Os(II)Pc]Â²â ») and the tetramethyltetra-pyridinoporphyrazine complexes of Pd(II) and Pt(II), ([Pd(II)2,3Tmtppa(-2)]â ´â º, [Pd(II)3,4Tmtppa(-2)]â ´â º, [Pt(II)2,3Tmtppa(-2)]â ´â º and [Pt(II)3,4Tmtppa(-2)â ´â º) have been prepared. [(CN)â‚‚Os(II)Pc]Â²â » is soluble in water at pH greater 4 without the formation of dimers. The [M(II)Tmtppa(-2)]â ´â º (M = Pd or Pt) show high solubility in water and are stable only in acidic pHs. The cyclic voltammetry of the MPc and [M(II)Tmtppa(-2)]â ´â º complexes prepared, is also reported. The interactions of amino acids I-histidine and I-cysteine with the [M(II)Tmtppa(-2)]â ´â º complexes of Pd(II) and Pt(ll) were studied. All the [M(Il)Tmtppa(-2)]â ´â º are readily reduced to the monoanion species [M(Il)Tmtppa(-3)]Â³â » in the presence of histidine and cysteine. The rate constants for the interaction of [M(Il)Tmtppa(-2)]â ´â º complexes ofPt(II) and Pd(II), with histidine and cysteine range from approximately 2 x 10â »Â³ to 0.26 dmÂ³ molâ »Â¹ sâ »Â¹. Kinetics of the interaction of [Co(Il)TSPc]â ´â » with amino acids, histidine and cysteine in pH 7.2 buffer were studied. The rate constants were found to be first order in both [Co(II)TSPc]â ´â » and the amino acid. The formation of [Co(III)TSPc]Â³â » in the presence of histidine occurred with the rate constant of 0.16 dmÂ³ molâ »Â¹ sâ »Â¹, whereas the formation of the [Co(I)TSPc]â µâ » species in the presence of cysteine gave the rate constant of 2.2 dmÂ³ moâ »Â¹ sÂ¹. The relative quantum yield (QÎ”) for singlet oxygen production by [(CN)â‚‚Os(Il)Pc]Â²â », and [(CN)â ´Ru(II)Pc]Â²â » in DMF using diphenylisobenzofuran (DPBF) and a chemical quencher were determined. The quantum yield values were obtained as 0.39 Â± 0.05 , and 0.76 Â± 0.02 for [(CNâ‚‚Os(II)Pc]Â²â » and [(CN)â‚‚Ru(II)Pc]Â²â » respectively. The differences in quantum yield values have been explained in terms of donor abilities of both the central metal and the axial ligands.
Keywords: Phthalocyanines; Platinum group